CONTRIBUTION TO THE FAUNA OF CYNIPID GALL WASPS (HYMENOPTERA: CYNIPIDAE) OF MT. OBLA GLAVA (SERBIA) (Acta Entomologica Serbica, 2018)
During 2005-2017 on Mt. Obla Glava (southeastern Serbia), 30 species of gall wasps were recorded from two tribes [Cynipini (26) and Diplolepidini (4)] and 8 genera [Andricus (17 species), Diplolepis (4), Cynips (3), Neuroterus (2), Aphelonyx (1), Biorhiza (1), Dryocosmus (1), and Pseudoneuroterus (1)]. The highest number of species was found on Quercus pubescens (17), somewhat less on Q. frainetto (13) and Q. petraea (11), and the least on Q. cerris (6) and Rosa sp. (4). Andricus stefanii is the first record for Serbia. Localities, dates of gall collecting and host plants for all recorded species are given.